POLA GANTI RUGI LAHAN DALAM PEMBANGUNAN JALAN BARAMBANG TAMAIRANG DESA MUARA SIKABALUAN KABUPATEN KEPULAUAN MENTAWAI - Irwin Irwin (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the construction of the Barambang Tamairang road, Muara Sikabaluan Village, which was built in 2015 and approximately 6 km. Road measurements to be made for the construction of roads on agricultural land owned by the community with an agreement will be compensated for the community’s land with an agreement during a meeting at the village hall. The problem in the construction of the Barambang Tamairang road is that not all compensation has been resolved by the government. The purpose og this study is how the pattern of land compensation of the Barambang Tamairang road, Muara Sikabaluan Village, Mentawai Island Regency. The theory used in this research is the Exchange theory put forward by Peter Michael Blau. The method used in this study is a qualitative approach with a descriptive type to describe the problem under study. Retrieval of informant by purposive sampling with a total of 12 informant. There are two types of data in this study, namely primary data and secondary data. The research data was collected using observation, interview, and document study techniques. Data analysis was performed by collecting data, reducing data, presenting data and drawing conclusions with this research unit’s analysis group. Based on the results of research conducted, found in the process og land compensation in the construction of the Barambang Tamairang road, Muara Sikabaluan Village, Mentawai Island Regency: (1) Deliberation of Consensus, (2) Pattern of money compensation.